PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER) DAN RETURN ON ASSET (ROA) TERHADAP DIVIDEND PAYOUT RATIO (DPR) PADA INDUSTRI MANUFAKTUR SUB SEKTOR LOGAM DAN SEJENISNYA YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE TAHUN 2017-2020 - Pandiangan, Lady Avilla; Hasugian, Chandiny; Sitopu, Juwita Dearni; Lina; Juli Meliza (Journal Accounting International Mount Hope, 2024)
The purpose of this research is to see the influence of the Current Ratio (CR), Debt to Equity Ratio (DER) and Return On Asset (ROA) on the Dividend Payout Ratio (DPR) in the Metal and Similar Sub-Sector Manufacturing Industry listed on the Stock Exchange Inodenesia (BEI) for the 2017-2020 period. The type research, the data source in this research is secondary research. The population of this research was 17 companies that were included in the listed criteria, 2 companies did not publish regularly during the research period, 12 companies that experienced losses during the research period and registered companies minus the companies that experienced losses, the result was 3and multiplied by 4 years becomes 12. The data collection technique used in this research uses documentation techniques to collect secondary data from the annual financial reports of the Metals and Similar Sector for the period 2017-2020 based on the result of this research partially and simultaneously, namely the variable X Current Ratio (CR), Debt to Equity Ratio (DER) and Return On Asset (ROA) have a significant effect on the variables Y Dividend Payout Ratio (DPR). The result of the coefficient of determination show that dependent variable (Y) in this study by 56%, while the other 46% are influenced by other variables or factorc from outside the research.